Endogenous Serum IgG Antibodies to Clostridium difficile Toxin B Are Associated with Protection against C. difficile Infection Recurrence. (4th October 2017) - Kelly, Ciaran P; Poxton, Ian R; Shen, Judong; Railkar, Radha; Guris, Dalya; Dorr, Mary Beth
Abstract: Background: MODIFY I/II were global trials of the efficacy and safety of bezlotoxumab (BEZ), a monoclonal antibody (mAb) against C. difficile toxin B, alone and with actoxumab (ACT), a mAb against C. difficile toxin A. BEZ was superior to placebo (PBO) at preventing recurrent CDI (rCDI) in patients (patients) receiving antibacterials for CDI. The addition of ACT did not improve efficacy. The aims were to explore potential biomarkers for rCDI risk in the patients receiving PBO by measuring endogenous IgG Abs against Cd toxins A and B (eAb-A and eAb-B); it was expected that patients with low eAb levels might be at increased risk of rCDI. Methods: Serum samples were collected pre-dose (PRE), at Week 4, and Week 12 postdose. eAb titers were measured using an electrochemiluminescence immunoassay. Results were reported as <1:1000, 1:1000, 1:5000, 1:25000, and ≥1:125000. As there is no clearly defined immunological surrogate of efficacy for rCDI tied to a specific eAb-A or eAb-B level, eAb levels were arbitrarily categorized as low (≤1:1, 000), medium (1:5000), or high (≥1:25000). The rCDI rate was summarized by eAb category at each time point. Results: The proportion of patients with higher eAb-A and eAb-B titers increased following the initial CDI episode (Tables 1 and 2). There was no evident correlation between eAb-A titers and the rCDI rate at any time point. The proportion of patients who experienced rCDI within 12 weeks after randomization was highest in patients with low eAb-B titers PRE and at Week 4. rCDI rate in those with low eAb-B titer at all timepoints and in patients who had low titer only at PRE was similar. Conclusion: The rise in eAb-A and eAb-B titers over time is consistent with a convalescent humoral immune response to toxins A and B following CDI. The lack of correlation between eAb-A titers and rCDI is consistent with the lack of efficacy of ACT in prevention of rCDI. Conversely, higher eAb-B titers are associated with lower risk for rCDI, consistent with the efficacy of BEZ. 22.1% of patients with high eAb-B titers at PRE experienced rCDI. Therefore, eAb-B titers may have marginal utility as a biomarker for rCDI risk and are not likely to improve predictive value over clinical and demographic characteristics such as advanced age, compromised immunity, and CDI history. Disclosures: C. P. Kelly, TBD: Investigator, Speaker honorarium; J. Shen, Merck & Co., Inc.: Employee, may hold stock/hold stock options in the Company; R. Railkar, Merck & Co., Inc.: Employee, may own stock/hold stock options in the Company; D. Guris, Merck & Co., Inc.: Employee, may own stock/hold stock options in the Company; M. B. Dorr, Merck & Co., Inc.: Employee and Shareholder, may own stock/hold stock options in the Company